Emerging Developments in Microbiome and Microglia Research: Implications for Neurodevelopmental Disorders - Lebovitz, Yeonwoo; Ringel-Scaia, Veronica M.; Allen, Irving C.; Theus, Michelle H. (Frontiers in Immunology, 2018)
From immunology to neuroscience, interactions between the microbiome and host are increasingly appreciated as potent drivers of health and disease. Epidemiological studies previously identified compelling correlations between perinatal microbiome insults and neurobehavioral outcomes, the mechanistic details of which are just beginning to take shape thanks to germ-free and antibiotics-based animal models. This review summarizes parallel developments from clinical and preclinical research that suggest neuroactive roles for gut bacteria and their metabolites. We also examine the nascent field of microbiome-microglia crosstalk research, which includes pharmacological and genetic strategies to inform functional capabilities of microglia in response to microbial programming. Finally, we address an emerging hypothesis behind neurodevelopmental disorders, which implicates microbiome dysbiosis in the atypical programming of neuroimmune cells, namely microglia.